ANALISIS FUNDAMENTAL DAN KINERJA KEUANGAN PT.PLN (PERSERO) TAHUN 2019-2023 - Hidayat, Muhammad; Zahara, Siti; Mulyati, Sri; Jaya, Hendry (Universitas Riau Kepulauan, 2025)
This study aims to conduct a fundamental and financial performance analysis of PT PLN (Persero). The research employs a descriptive quantitative approach, utilizing secondary data in the form of financial statements downloaded directly from PT PLN (Persero)'s official website. The results indicate a negative operational performance in 2019. However, from 2020 to 2023, there has been improvement, although optimal efficiency has not yet been achieved. Revenue and EBITDA have increased, but profit margins have declined, suggesting that operational costs have risen at a faster rate than revenue. The Debt Service Coverage Ratio (DSCR) consistently demonstrates the company’s ability to meet its debt obligations. The Debt to Equity Ratio (DER), ranging between 64–71%, indicates a relatively secure position in managing its capital structure. Growth trends are positive and sustainable. Return on Assets (ROA) shows a positive trend, reflecting improved financial performance efficiency. Return on Equity (ROE) also indicates a healthy and positive growth trend, suggesting the company is increasingly effective in utilizing equity to generate profits. Earnings Per Share (EPS) has exhibited a very positive growth trend since 2020.